The Effectiveness of Jigsaw and STAD Techniques in Teaching Reading Comprehension to The Ninth Grade Students with Different Levels of Motivation at a State Junior High School in Semarang - Prima Kismaning Diah; Sri Wuli Fitriati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study investigated the effectiveness of the Jigsaw and STAD (Student Teams Achievement Division) techniques in teaching reading comprehension to ninth-grade students with different levels of motivation at a state junior high school in Semarang during the 2025/2026 academic year. Employing a quasi-experimental design, the study involved 66 students divided into two experimental groups: one taught using the Jigsaw technique and the other using the STAD technique. Data were collected through a motivation questionnaire, pre-tests, post-tests, and triangulated with students’ perceptions and the teacher’s reflection. The findings revealed that both Jigsaw and STAD significantly improved students’ reading comprehension. Students with high motivation achieved higher post-test scores than those with low motivation in both techniques, indicating that motivation plays a crucial role in learning outcomes. However, the Two-Way ANOVA showed no significant interaction between teaching technique and motivation level (p = 0.777 > 0.05), suggesting that the effectiveness of both techniques was consistent across motivation levels. In conclusion, the Jigsaw and STAD techniques are effective, inclusive, and adaptable cooperative learning models that enhance students’ reading comprehension regardless of motivation level.